Abstract versus Causal Explanations?. Issue 2 (2nd April 2016) - Reutlinger, Alexander; Andersen, Holly
ABSTRACT: In the recent literature on causal and non-causal scientific explanations, there is an intuitive assumption (which we call the 'abstractness assumption') according to which an explanation is non-causal by virtue of being abstract. In this context, to be 'abstract' means that the explanans in question leaves out many or almost all causal microphysical details of the target system. After motivating this assumption, we argue that the abstractness assumption, in placing the abstract and the causal character of an explanation in tension, is misguided in ways that are independent of which view of causation or causal explanation one takes to be most accurate. On major accounts of causation, as well as on major accounts of causal explanation, the abstractness of an explanation is not sufficient for it being non-causal. That is, explanations are not non-causal by dint of being abstract.